Human immunodeficiency virus type 1 RNA Levels in different regions of human brain: Quantification using real-time reverse transcriptase-polymerase chain reaction - Kumar, Adarsh M; Borodowsky, Irina; Fernandez, Benny; Gonzalez, Louis; Kumar, Mahendra (Journal of neurovirology, 2007)
Human immunodeficiency virus type 1 (HIV-1) enters the central nervous system shortly after the infection and becomes localized in different regions of the brain, leading to various neurological abnormalities including motor disorders and neurocognitive deficits. Although HIV-1-associated functional abnormalities of the central nervous system (CNS) can be evaluated during life by using various test batteries, HIV-1 virus concentration in different brain regions can be measured only after death. The tissues obtained at autopsy provide a valuable source for determining the role of various factors, including that of HIV-1 viral load in the CNS, that may contribute to the regional CNS neuropathogenesis. For this study, we obtained from the National Institutes of Health-sponsored National NeuroAIDS Tissue Consortium (NNTC) the tissues from different brain regions collected at autopsy of HIV-1-positive (N = 38) and HIV-negative (N = 11) individuals, with postmortem intervals of 2 to 29 h, and measured HIV-1 RNA concentration in the frontal cortex, frontal cortex area 4, frontal cortex area 6, basal ganglia, caudate nucleus, putamen, globus pallidus, substantia nigra, and cerebrospinal fluid. Because HIV-1+ individuals were infected with the virus for up to 21 years and the majority of them had used highly active antiretroviral therapy (HAART), we used highly sensitive real-time reverse transcriptase-polymerase chain reaction (RT-PCR) assay in order to detect a wide dynamic range of HIV-1 RNA with lower detection limit of a single copy. The primers and probes were from the long terminal repeat (LTR) region of HIV genome for achieving higher specificity and sensitivity of detection and amplification. Our results demonstrate a wide variation in the concentration of HIV-1 RNA in different brain regions (5.51 and 8,144,073; log10 0.74 and 6.91 copies/g tissue), and despite the high specificity and sensitivity of this method, viral RNA was not detected in 50% of all the samples, and in 30% to 64% of samples of each region of HIV-1+ individuals. However, the highest concentration of viral RNA was found in the caudate nucleus and the lowest concentration in the frontal cortex and cerebrospinal fluid. The viral RNA was undetectable in all samples of HIV-negative individuals.